Pengaruh Media Koperasi berbantuan Web Based Terhadap Minat Berkoperasi Mahasiswa - Afief Maula Maula; Dini Riani; Ani Setiani (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
This study aims to determine the effect of Web-Based assisted cooperative media on students' interest in cooperatives. The population is 69 students of the Pasundan University Economics Education Study Program. The analysis used is simple linear regression analysis using the IBM SPSS Statistics Version 26 program. The results of the study show a simple linear regression analysis which produces Y = 9.635 + 0.836x, which means that there is an increase of 9.635 from Web-Based assisted cooperative media, the interest in cooperatives will increase or an increase of 0.836 while the results of the coefficient of determination show that there is an influence of Web-Based assisted cooperative media on the interest in cooperative Economics Education FKIP Unpas students of 57.9% which is included in the fairly strong category and 42.1% is influenced by other factors. Keywords: cooperative, web based, interest